Parametric analysis of venturi-type microbubble generator and the bubble fragmentation dynamics - Yi Zhou; Jingyu Cui; Zhen Chen; Jiancong Liu; Lipeng He; Wei Fan; Mingxin Huo (Desalination and Water Treatment)
Venturi-type tubes facilitate efficient microbubble generation, enhancing gas-liquid mixing, mass transfer, and reactions in wastewater treatment. However, the demand for high transfer efficiency with low energy consumption necessitates advancements in the parametric analysis of generators. This study presents a novel microbubble generator that integrates a suction chamber with a Venturi system. Through a comprehensive analysis of suction performance, gas-phase transport modes, and bubble collapse kinetics, we analyzed structural parameters using computational fluid dynamics simulations. The effective design features a centrally positioned nozzle, an air inlet at 2 mm depth, and a 12.5° divergence angle. Simulations indicated that a single bubble at the throat of the generator undergoes significant kinetic energy reduction and pressure energy increase in the expansion section, leading to pronounced tearing and deformation from inhomogeneous turbulence, resulting in smaller bubbles reduced to approximately 1/20 of their initial volume. Based on these analysis results, a laboratory-scale bubble generator was constructed, with flow tests demonstrating bubble sizes under 300 μm. Notably, the dissolved oxygen concentration in water treated by the generator was 12.6 % above the saturated level, showcasing superior oxygen enrichment compared to traditional aeration methods. This study provides valuable insights for advancing micro- and nano-bubble generation technologies.